Antagonization of the Nogo-Receptor 1 Enhances Dopaminergic Fiber Outgrowth of Transplants in a Rat Model of Parkinson’s Disease - Seiler, Stefanie; Di Santo, Stefano; Andereggen, Lukas; Widmer, Hans R. (Frontiers in Cellular Neuroscience, 2017)
Intrastriatal transplantation of fetal human ventral mesencephalic dopaminergic neurons is an experimental therapy for patients suffering from Parkinson’s disease. The success of this approach depends on several host brain parameters including neurotrophic factors and growth inhibitors that guide survival and integration of transplanted neurons. While the potential of neurotrophic factors has been extensively investigated, repression of growth inhibitors has been neglected, despite the significant effects reported in various CNS injury models. Recently, we demonstrated that infusion of neutralizing antibodies against Nogo-A into the lateral ventricles of hemi-parkinsonian rats significantly enhanced graft function. Since the Nogo-receptor 1 also interacts with other neurite growth inhibitors, we investigated whether a direct antagonization of the receptor would result in more robust effects. Therefore, rats with unilateral striatal 6-hydroxydopamine lesions were grafted with ventral mesencephalic tissue in combination with intraventricular infusions of the Nogo-receptor 1 antagonist NEP1-40. Transplanted rats receiving saline infusions served as controls. To test whether NEP1-40 treatment alone affects the remaining dopaminergic striatal fibers, rats with unilateral striatal 6-hydroxydopamine lesions were infused with NEP1-40 or saline without receiving a transplant. Motor behavior was assessed prior to the lesion as well as prior and one, three and five weeks after the transplantations. At the end of the experimental period the number of graft-derived dopaminergic fibers growing into the host brain, the number of surviving dopaminergic neurons and graft volume were analyzed. In rats without a transplant, the density of dopaminergic fibers in the striatum was analyzed. We detected that NEP1-40 treatment significantly enhanced graft-derived dopaminergic fiber outgrowth as compared to controls while no effects were detected for graft volume and survival of grafted dopaminergic neurons. Notably, the enhanced dopaminergic fiber outgrowth was not sufficient to improve the functional recovery as compared to controls. Moreover, NEP1-40 infusions in hemi-parkinsonian rats without a transplant did not result in enhanced striatal dopaminergic fiber densities and consequently did not improve behavior. In sum, our findings demonstrate that antagonization of the Nogo-receptor 1 has the capacity to support the engraftment of transplanted mesencephalic tissue in an animal model of Parkinson’s disease.